Complete mitochondrial genome and phylogenetic analysis of the copper shark Carcharhinus brachyurus (Günther, 1870). Issue 6 (3rd June 2021) - Kim, Sang Wha; Park, Seon Young; Kwon, Hyemin; Giri, Sib Sankar; Kim, Sang Guen; Kang, Jeong Woo; Kwon, Jun; Lee, Sung Bin; Jung, Won Joon; Lee, JunMo; Park, Se Chang; Kim, Ji Hyung
Abstract: Copper shark ( Carcharhinus brachyurus Günther, 1870) is one of the most widely distributed but least known species in the family Carcharhinidae. Herein, we report the first complete mitogenome of C. brachyurus . The overall structure of the 16, 704 bp C. brachyurus mitogenome was similar to that of other Carcharhinus species and showed the highest average nucleotide identity (97.1%) with the spinner shark ( Carcharhinus brevipinna ). Multigene phylogeny using 13 protein-coding genes (PCGs) in the mitogenome resolved C. brachyurus clustered with other species within the genus; the overall tree topology was congruent with recent phylogenetic studies of this species. These results provide important information for conservation genetics and further evolutionary studies of sharks.